Quality health care in Indian setup: an ear, nose, throat outpatient department-based approach for quality health care indicators - Joshi, Himanshu; Sahoo, Satyanjaya; Kumar, Vikas (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: In this era doctor patient relationship facing hard times, especially in Indian setup. It is immensely evident in form of increasing lawsuits and violence against doctors. This brings patient centred approach with patient satisfaction into picture and further leads to concepts of quality health care. There is raised attention on enhancing the quality of life through the quality council of India. Here is an attempt to look for any causal association with the help of some routine indicators which if modified can lead to better state of doctor patient relationship. Methods: This study has taken patient satisfaction into consideration with the help of quality care parameters at ear, nose, throat (ENT), outpatient department in Indian setup. These indicators are based on parameters divided into hospital domain and doctor domain and each parameter is graded on 5-point Likert scale. Results: Score under doctor domain are significantly high statistically. Examination and communication by doctor (domain) are the parameters which scored the most. Under hospital domain the highest preference by patients in terms of score was given to hygiene and sanitation of hospital. Conclusions: Quality health care is multifactorial and parameters under hospital domain and doctor domain are interdependent to much extent. It has been concluded statistically that examination and communication by doctor derives a better sense of trust and doctor patient relationship significantly.